Compounds identified in plant extracts applied to agriculture and seed treatment/Compostos identificados em extratos vegetais aplicados na agricultura e no tratamento de sementes - da Silva Carvalho, Ricardo; da Silva, Mariana Altenhofen; Borges, Maria Teresa Mendes Ribeiro; Fo (Ciência rural, 2024)
Plant extracts effects have been regarded and proven in researches under different applications in agriculture, including seed treatment. The plant extracts effectiveness is attributed to the presence of certain classes of compounds; therefore, studies that aim to identify and quantify these composites, which are present in plant extracts used in agriculture, are important, as well as the seed treatment. This research aimed to understand and describe through a systematic review, what were the main carried approaches, classes and identified compounds in studies with plant extracts to different applications in agriculture and the seed treatment. The period 2015 to 2020 was the one that exposed the higher research publication indexes, considering the theme under analysis, plant extracts in agriculture, seeking to identify or quantify the presence of metabolic composites, indicating a growing interest in this theme. Such studies pursued identifying and/or quantifying the compounds that are present in the plant extracts. The phenolic compounds constitute the priority class of metabolites to different functions, effects and applications in agriculture, mainly in seed treatment. The terpenes present a substantial potential as bioinsecticides to agriculture. Plant species that are rich in phenolic and terpenes compounds are a significant source of alternative control in the protection of the productive system. Key words: secondary metabolites, terpenes, seed treatment, alternative control. Efeitos de extratos vegetais têm sido apontados e comprovados em pesquisas sob diferentes aplicações na agricultura, incluindo o tratamento de sementes. A eficácia de extratos vegetais é atribuída a presença de certas classes de compostos, logo, sendo importante estudos que visam a identificação e quantificação destes compostos presentes em extratos de plantas usados na agricultura, bem como para o tratamento de sementes. Objetivou-se compreender e descrever, por meio de uma revisão sistematizada, quais as principais abordagens realizadas, classes e compostos identificados em estudos com extratos vegetais para diferentes aplicações na agricultura e no tratamento de sementes. O período 2015 a 2020 foi o que apresentou os maiores índices de publicações de pesquisas que exploram extratos vegetais na agricultura, buscando identificar e, ou quantificar os compostos presentes nos extratos vegetais. Os compostos fenólicos constituem a classe prioritária de metabólitos para diferentes funções, efeitos e aplicações na agricultura, principalmente no tratamento de sementes. Os terpenos apresentam grande potencial como bioinseticidas para a agricultura. Espécies de plantas ricas em compostos fenólicos e terpenos são fontes potenciais para controle alternativo na proteção de sistemas produtivos. Palavras-chave: metabólitos secundários, terpenos, tratamento de sementes, controle alternativo.